Peningkatan Literasi Kesehatan Reproduksi melalui Intervensi Edukatif dan Pemeriksaan Kesehatan pada Mahasiswa Kedokteran UMPR: Enhancing Reproductive Health Literacy through Educational Interventions and Medical Checkups among Medical Students of UMPR - Qamariah, Nurul; Faradila, Faradila; Badjeber, Alvia Novita; Adhyatma, Mirza; Tansuria, Norman Jesse; Handoko, Arif; Brillianty, Ricka; Purbawa, Putu Aditya Adi; Thaihutu, Yhohan Ziantprayogi; Pramitasari, Putu Andina; Safitri, Rika Arfiana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Adolescents' limited understanding of reproductive health can lead to long-term health risks. This community service activity, organized by the Faculty of Medicine at Universitas Muhammadiyah Palangkaraya in collaboration with the Kereng Bangkirai Health Center, aimed to improve reproductive health literacy among adolescents through education and health screening. The program involved 33 second-semester medical students and included a pretest, interactive seminar, posttest, and health examinations covering vital signs, body mass index, blood glucose, and HBsAg screening. Findings revealed that 27.3% of participants were overweight, 18.2% were prehypertensive, and 15.2% had elevated random blood glucose, while all tested negative for hepatitis B. The average knowledge score increased from 89.9% to 91.5%, with the most significant gains in understanding menstruation and nocturnal emission. These results highlight the effectiveness of campus-based educational interventions and the need to promote healthy lifestyles early on. The activity also emphasizes the role of medical students as change agents in disseminating reproductive health knowledge in the community.